Proposing Novel Schema for Downstream Using Multiple OLTs in EPON System - Beybutyan, Davit V. (Mathematical Problems of Computer Science, 2021)
The paper proposes a new schema for downstream using multiple OLT mechanisms in EPON system. In the proposed mechanisms a new DBA algorithm is used, so-called CDBA-Controlled Dynamic Bandwidth Allocation, this controls the assigned bandwidth for each OLT. We proposed an architecture which also comforts the system reliability; in case of network failure another OLT will be able to recover the system in a short period of time. It also allows the unused bandwidth of one OLT to be used by the other OLT. In the future, companies can provide their services without deploying another PON.